Second generation stationary digital breast tomosynthesis system with faster scan time and wider angular span. Issue 9 (25th July 2017) - Calliste, Jabari; Wu, Gongting; Laganis, Philip E.; Spronk, Derrek; Jafari, Houman; Olson, Kyle; Gao, Bo; Lee, Yueh Z.; Zhou, Otto; Lu, Jianping
Abstract : Purpose: The aim of this study was to characterize a new generation stationary digital breast tomosynthesis system with higher tube flux and increased angular span over a first generation system. Methods: The linear CNT x‐ray source was designed, built, and evaluated to determine its performance parameters. The second generation system was then constructed using the CNT x‐ray source and a Hologic gantry. Upon construction, test objects and phantoms were used to characterize system resolution as measured by the modulation transfer function (MTF), and artifact spread function (ASF). Results: The results indicated that the linear CNT x‐ray source was capable of stable operation at a tube potential of 49 kVp, and measured focal spot sizes showed source‐to‐source consistency with a nominal focal spot size of 1.1 mm. After construction, the second generation (Gen 2) system exhibited entrance surface air kerma rates two times greater the previous s‐DBT system. System in‐plane resolution as measured by the MTF is 7.7 cycles/mm, compared to 6.7 cycles/mm for the Gen 1 system. As expected, an increase in the z‐axis depth resolution was observed, with a decrease in the ASF from 4.30 mm to 2.35 mm moving from the Gen 1 system to the Gen 2 system as result of an increased angular span. Conclusions: The results indicate that the Gen 2 stationary digital breast tomosynthesis system, which has a larger angular span, increased entrance surface air kerma, and faster image acquisition time over the Gen 1 s‐DBT system, results in higher resolution images. With the detector operating at full resolution, the Gen 2 s‐DBT system can achieve an in‐plane resolution of 7.7 cycles per mm, which is better than the current commercial DBT systems today, and may potentially result in better patient diagnosis.